A Comparative Study of Fibroblast Behaviors under Cyclic Stress Stimulus and Static Culture on 3D Patterned Matrix - Zhao, Mingyan; Li, Lihua; Li, Bo; Wu, Di; Zhou, Changren; Tian, Ye (Journal of bionics engineering, 2013)
Mechanical stress and patterned surface of the scaffolds has been recognized as a crucial factor in determining cell func- tionality and tissue development, which in turn can direct the cell responses. In this study, fibroblasts M-3T3 in three-dimensional （3D） honeycomb patterning Chitosan/Poly（L-Lactic Acid） （CS/PLLA） composites was stimulated by a 15% sinusoidal （1 Hz） strain applied by a biodynamic test instrument. The effects of mechanical stimulus on the cell proliferation and basic Fibroblast Growth Factor （bFGF） secretion were studied in comparison to the non-strain groups and blank control. Results show that fibroblasts are able to sense the mechanical stimulation and respond, resulting in a time dependent increase of bFGF secretion and promoting cell proliferation. Moreover, the cells seeded in the scaffolds showed a higher cell proliferation and bFGF secretion. These findings support the hypothesis that suitable mechanical stimulus has positive effect on fibroblasts, and such a 3D honeycomb patterned scaffold may play a positive role in regulating cell behaviors in vitro.